Preoperative Chronic Pain as a Risk Factor for Early Postoperative Cognitive Dysfunction in Elderly Patients Undergoing Hip Joint Replacement Surgery: A Prospective Observational Cohort Study - Huai, Xiaorong; Jiao, Yingfu; Gu, Xiyao; Zhu, Huichen; Chen, Lingke; Fan, Yichen; Yu, Weifeng; Su, Diansan; Xie, Hong (Frontiers in Neuroscience, 2021)
Background: Although there is high overall success rate of major joint replacement surgery, postoperative cognitive dysfunction (POCD) is a very common complication after surgery, increasing morbidity and mortality. Identifying POCD risk factors would be helpful to prevent and decrease the occurrence of POCD. We hypothesised that preoperative chronic pain increases the risk of POCD. Methods: A single-centre, observational, prospective cohort study was conducted from January 2018 to March 2020. All consecutive elderly patients (>65 years) who underwent elective hemiarthroplasty or total hip arthroplasty with general anaesthesia by the same surgeon were enrolled. The patients underwent neuropsychological testing preoperatively and at 7 days and 2 months postoperatively. To determine POCD, a nonsurgical control group was recruited from the general community. Results: Of the 141 patients who finished the neuropsychological testing 7 days after surgery, 61 (43.2%) had preoperative chronic pain. Of the 61 patients, 17 (27.9%) developed POCD; of the 79 patients with no chronic pain, 10 (12.7%) had developed POCD by 7 days after surgery. Multivariate logistic regression analysis identified preoperative chronic pain as a risk factor of POCD assessed 7 days after surgery (odds ratio, 3.335; p = 0.022). There was no significant difference in the POCD incidence 2 months after surgery between patients with and without preoperative chronic pain. Conclusions: Preoperative chronic pain was a risk factor of developing POCD within 7 days after surgery in elderly patients following hip joint replacement surgery.